2023
DOI: 10.3390/polym15020254
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress of Non-Isocyanate Polyurethane Foam and Their Challenges

Abstract: Polyurethane foams (PUFs) are a significant group of polymeric foam materials. Thanks to their outstanding mechanical, chemical, and physical properties, they are implemented successfully in a wide range of applications. Conventionally, PUFs are obtained in polyaddition reactions between polyols, diisoycyanate, and water to get a CO2 foaming agent. The toxicity of isocyanate has attracted considerable attention from both scientists and industry professionals to explore cleaner synthesis routes for polyurethane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 69 publications
0
11
0
Order By: Relevance
“…However, the conventional method that involves the production of NIPU from bicyclic carbonate and polyamine does not naturally produce foaming agents. 70 Researchers recently used a new blowing agent to make high-density NIPU foams with large interconnected cells. 71 Common blowing agents can worsen fire behavior, so there is interest in using nonflammable alternatives.…”
Section: Fully Biobased Polyestermentioning
confidence: 99%
“…However, the conventional method that involves the production of NIPU from bicyclic carbonate and polyamine does not naturally produce foaming agents. 70 Researchers recently used a new blowing agent to make high-density NIPU foams with large interconnected cells. 71 Common blowing agents can worsen fire behavior, so there is interest in using nonflammable alternatives.…”
Section: Fully Biobased Polyestermentioning
confidence: 99%
“…Polyurethane (PU) foams have been widely applied in various industries such as building thermal insulation, packaging, and comfort items (matresses, seats, pillows, ...) and so on due to their excellent thermal insulating properties, light weight, excellent mechanical properties and low costs . It is reported that about 60% of the PU products are used to produce PU foams and the production of PU foams is expected to grow from 42.8 billion US dollars in 2021 to 61.5 billion US dollars by 2026. , However, the traditional PU foams are generally synthesized by utilizing the rapid reaction of water and isocyanate to release CO 2 as the blowing agent associated with simultaneous formation of urethane blocking units through reaction between polyols and isocyanate. The application of toxic isocyanate in the synthesis of PU foams has led to increasing health and environmental concerns as well as regulatory scrutiny, which has driven the industry and academic circles to develop non-isocyanate polyurethane (NIPU) foams …”
Section: Introductionmentioning
confidence: 99%
“…Reducing isocyanate concentrations in foam formulations increases safety and lowers cost. Isocyanates are toxic chemicals that irritate mucous membranes, resulting in severe and chronic asthma symptoms in individuals who have prolonged exposure, in some cases resulting in death. , However, the current isocyanate alternatives cannot fully meet the requirements for industrial free-rise foams and it is not possible to completely eliminate the use of isocyanate altogether. Therefore, it is important to explore methods for reducing the amount of isocyanates used in foam production which can be immediately implemented in industry, while isocyanate replacement research is ongoing.…”
Section: Introductionmentioning
confidence: 99%